Synthesis of Some Mono- and Disaccharide-Grafting Phthalazine Derivatives and Some New Se-Nucleoside Analogues: Antibacterial Properties, Quantum Chemical Calculations, and Cytotoxicity - El-Shamy, I E; Hleli, E; Alsheikh, A A; Yawer, M A; El-Hashash, M A; Dybal, J; Abdel-Mohsen, A M (Molecules (Basel, Switzerland), 2022)
A highly efficient and versatile synthetic approach for the synthesis of 4-(pyren-1-ylmethyl)-1-(d-glycosyloxy) phthalazine nucleosides 11a,b, 13, β-S-nucleosides 16, 18, 20, and acyclo C-nucleosides 23a,b, 24, 25 and 27a-f was described and fully characterized. Furthermore, a series of desired new nucleoside analogues containing Se of 4-(pyren-1-ylmethyl) phthalazine-1(2H)-selenone 28-33 were synthesized. The structures of all reported compounds were confirmed by IR, 1H-NMR, 13C-NMR, MS and elemental analysis. All compounds have been screened for their antibacterial and antifungal activities. Maximum activity was shown by 20 and 33a comparable to the standard drugs with lower toxicity. The cytotoxicity of the selected compound was measured and evaluated. The energy gap between the highest occupied molecular orbital and lowest unoccupied molecular orbital was calculated using theoretical computations to reflect the chemical reactivity and kinetic stability of the synthesized compounds. Using density functional theory (DFT), electronic parameters such as the highest occupied and lowest unoccupied molecular orbitals (HOMO and LUMO) and the molecular electrostatic potential (MEPS) were calculated. On the basis of different studied structures, these properties were computed in order to elucidate the chemical reactivity and the kinetic stability. Obviously, the band gap energy (Eg) of structures studied reveals that the lowest band gap obtained for the structure 16-a indicates that it has the highest chemical reactivity and lowest kinetic stability.
Keywords: S-nucleosides; magnetická rezonanční spektroskopie; Nucleosides; nucleoside analogues; Models, Molecular; molekulární modely; ftalaziny; Anti-Bacterial Agents; nukleosidy; biocompatibility; Quantum Theory; mono/disaccharides; quantum calculations; antibacterial; Magnetic Resonance Spectroscopy; Phthalazines; antibakteriální látky; kvantová teorie